Serum concentrations of Dickkopf-1 protein are increased in patients with multiple myeloma and reduced after autologous stem cell transplantation - Politou, M.C.; Heath, D.J.; Rahemtulla, A.; Szydlo, R.; Anagnostopoulos, A.; Dimopoulos, M.A.; Croucher, P.I.; Terpos, E. (International Journal of Cancer, 2006)
Dickkopf-1 (DKK-1) protein, a soluble inhibitor of Wnt signalling, has been implicated in the pathogenesis of myeloma bone disease through the suppression of osteoblast differentiation. In this study, serum concentrations of DKK-1 were measured in 50 myeloma patients (32 at diagnosis and 18 before and after autologous stem cell transplantation (ASCT), 18 patients with monoclonal gammopathy of undetermined significance (MGUS), and 22 healthy controls. Serum DKK-1 levels were increased in MM at diagnosis compared with MGUS (mean ± SD: 67 ± 54 ng/mL vs. 38 ± 13 ng/mL; p = 0.006) and controls (31 ± 11 ng/mL; p = 0.02), while there was no difference between MGUS patients and controls. Although patients with stage 2 and 3 myeloma had higher DKK-1 values than stage 1 patients (79 ± 63 vs. 40 ± 13; p = 0.005), no significant correlation between serum DKK-1 and myeloma bone disease was observed. Myeloma patients before ASCT also had increased levels of DKK-1 (63 ± 77 ng/mL; p = 0.03) compared with controls, supporting the notion that DKK-1 may be responsible for the suppressed osteoblast activity even in patients with low tumor burden. After ASCT, there was a sustained decrease in DKK-1 levels over time, while bone formation markers elevated, suggesting that the reduction of DKK-1 levels after ASCT may correlate with the normalization of osteoblast function. These results could provide the basis for developing agents that block DKK-1, thus restoring osteoblast function and counteracting the increased osteoclastogenesis observed in myeloma. © 2006 Wiley-Liss, Inc.
Keywords: Autologous stem cell transplantation; Bone disease; Dickkopf-1 (DKK-1); multiple myeloma; Osteoblasts